Giga-Cycle Fatigue Behavior of the Nuclear Structure of 316L Weldments - Xiong, Zhihong; Peng, Engao; Zeng, Lianghua; Xu, Qirong (Frontiers in Energy Research, 2021)
Some components made of 316L stainless steel in nuclear reactors are connected by welding, and these are under giga-cycle fatigue loading. Therefore, the giga-cycle fatigue behavior of 316L weldments, which are fabricated by Laser Beam Welding (LBW) and Gas Tungsten Arc Welding (GTAW), were investigated using an ultrasonic fatigue testing system. The results indicate that the fatigue strength of LBW-made weldments is almost the same as that of GTAW-made weldments even though the microstructure and mechanical properties of the weldments are different. For the LBW-made specimens, the LBW-induced internal pores with a diameter range of about 89–270 μm were observed in the fracture surface. However, an obvious decrease in fatigue life was not observed in such cases. For the GTAW-made specimens, the quality requirement of the weld seam has to be more strict to prevent fatigue strength from decreasing. The fatigue failure mode of the GTAW-made specimens is the same as that of LBW-made specimens in the high-cycle fatigue regime but different in the giga-cycle fatigue regime.